Management of Educator and Education Staff in The Islamic Education Management Study Program Faculty of Tarbiyah IAIN Bone - Abu Bakar, Abu Bakar; Fitriani, Fitriani; Amin, Arifah (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This research aims to describe the management process of educator and education staff consisting of planning, organizing, actuating and controlling. This research uses a qualitative approach with data collection techniques are the method of observation, interviews and documentation. The data that has been collected is then analyzed through the stages of data reduction, data display and drawing conclusions. The results of the research are 1) Planning of educator and education staff in the Islamic Education Management study program, Faculty of Tarbiyah IAIN Bone is carried out by analyzing needs, researching problems, collecting data and information through the coordination of each leader, a series of actions carried out based on SOP, and finding solutions together to be used as the next reference. 2) Organizing of educator and education staff in the Islamic Education Management study program of the Tarbiyah Faculty of IAIN Bone is regulated based on the applicable IAIN Bone statutes and ortakers, the recruitment and placement of educator and education staff proposed from the institute and regulated by the central government. 3) Actuating of educator and education staff in the Islamic Education Management study program, Faculty of Tarbiyah IAIN Bone is supported by giving examples from leaders, guidance through training and BIMTEK, fairly effective communication, giving motivation in the form of rewards and punishments, giving facilities and infrastructure for education staff that are adequate and still sought to be the best for educator. 4) Controlling of educator and education staff in the Islamic Education Management study program, Faculty of Tarbiyah IAIN Bone is carried out by monitoring and evaluating every study program, directly from the leadership, and various routine reports as a form of real output. Then followed up with problem solving together.